(untitled) (International Journal of Medical and Surgical Sciences, 2024)
Orijin bitters, Hibiscus sabdariffa and Zingiber officinale roscoe have been reported to possess various medicinal properties. The aim of the study is to evaluate their effects on the kidney of adult wistar rats. Methodology: thirty rats were randomly divided into 6 groups, each having 5 rats. Group 1 received distilled water, group 2, 70cl/70kg/bw orijin bitters, group 3, orijin bitters and 200mg/kg/bw Hibiscus sabdariffa calyx aqueous extract, group 4, orijin bitters and 500mg/kg/bw Hibiscus sabdariffa calyx aqueous extract, group 5, orijin bitters and 200mg/kg/bw officinale rhizome aqueous extract, group 6, orijin bitters and 500mg/kg/bw Zingiber officinale rhizome aqueous extract over a 21- day period. After administration, the rats were sacrificed and the kidney harvested for biochemical and histological analysis. Results: Orijin bitters altered renal function, indicated by elevated level of malondialdehyde and decreased level of superoxide dismutase, catalase and glutathione, along with histopathological changes such as glomerular atrophy and tubular degeneration compared to the control. The result was not statistically significant (P < 0.05). Conversely, aqueous extracts of Hibiscus sabdariffa calyx and Zingiber officinale rhizome exhibited antioxidant properties, reducing oxidative stress and mitigating renal damage compared to the orijin bitters group only. Although the result was not statistically significant (P < 0.05). Conclusion: Orijin bitters may have nephrotoxic effects, while Hibiscus sabdariffa and Zingiber officinale may offer protective benefits, due to their antioxidant properties.